Bioeconomic benefits of managing fishing effort in a coexisting small- and large-scale fishery game. (23rd June 2021) - de Azevedo, Eric Zettermann Dias; Pintassilgo, Pedro; Dantas, David Valença; Daura-Jorge, Fábio Gonçalves
Abstract: Fishing systems provide employment, income generation, poverty alleviation, and food security. The coexistence of small-scale fisheries (SSFs) and large-scale fisheries (LSFs) increases management complexity. Management actions have ecological and social implications that must be addressed carefully. We applied a bioeconomic game-theoretical model to the four-gear mullet fishery in southern Brazil—one industrial LSF (purse seine) and three artisanal SSFs (gillnet, beach seine, and drift net). All fishing gears target adult individuals during mullet's reproductive migration. First, we explored whether the current fishing efforts of all fishing gears could persist over time. Second, we investigated their interactions through a non-cooperative game. Finally, we studied the response of these interactions when fishing effort was restricted. We found that when the current fishing effort was maintained, the stock reduced to 26.4% of its capacity in 25 years. In addition, under non-cooperation, the traditional beach seine fleet exited the fishery. Interestingly, the constrained scenario had a coexistence output with increasing values for the final stock size and the per capita labour income, suggesting that limiting fishing effort can maintain all fishing gears in the fishery with social and ecological benefits.